Sukuk Dan Kontribusinya Dalam Pembiayaan Pembangunan - Husnul Khatimah (Optimal: Jurnal Ekonomi dan Kewirausahaan, 2017)
This study analyzes the role of sukuk in national economic development. During this time the source of development financing consists of several kinds including taxes, bonds, foreign debt and Islamic bonds (sukuk). Sukuk has been developed in Indonesia since 2002 (published Indosat) and is still growing and the number of issuers are even greater. The research method using descriptive quantitative, data source in this research is secondary data obtained, balance of payments in the government, the state budget. This study uses a quantitative descriptive approach. Data were processed using matrix comparison of the performance of sukuk and conventional bonds to finance national development. The role and contribution of sukuk to finance the construction has been increasing. In 2011 amounted to 34% of financing needs are met through sukuk. Until 2016 the proportion was 60%. Instead the role of foreign debt be decreased. In 2011 only 7%, and by 2016 the portion close to 0%.